2021
DOI: 10.1108/ijoa-07-2020-2341
|View full text |Cite
|
Sign up to set email alerts
|

Using positive deviance to enhance employee engagement: an interpretive structural modelling approach

Abstract: Purpose Organisations today seek high engagement levels from their employees for their superior performance amid the highly competitive environment. The purpose of this paper is to examine the role of positive deviance facilitators (PDFs) in enhancing employee engagement at work. Design/methodology/approach The study adopts the interpretive structural modelling (ISM) and Matrice d’Impacts Croisés-Multiplication Appliquée á un Classement (MICMAC) analysis to understand the process of how positive deviance may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Even in the genre of sports, athletes' overconformity to sports ethic can be seen through the lens of PD (Hughes & Coakley, 1991). Among the recent papers, we find PD is used as a lens to understand employee engagement (Sharma, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 96%
“…Even in the genre of sports, athletes' overconformity to sports ethic can be seen through the lens of PD (Hughes & Coakley, 1991). Among the recent papers, we find PD is used as a lens to understand employee engagement (Sharma, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 96%
“…Compared to Kahn’s engagement, Schaufeli et al ’s (2002) concept of work engagement received substantial attention from the scholars’ fraternity and narrowed down from engagement to the organisational setting, and its measures were developed. Since 2002, many authors confirmed that work engagement relates to numerous workplace outcomes such as increased organisational commitment (Teo et al , 2020; Saks, 2006; Demerouti et al , 2001), job satisfaction (Saks, 2006; Schaufeli and Bakker, 2004), individuals’ performance (Alfes et al , 2013), overall well-being and health outcomes (Sharma, 2021; Imran and Shahnawaz, 2020) and decreased intention to turnover (Chen et al , 2018; Shantz et al , 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In line with SET, implementation of HCWS highlights decision-making involvement, job security, training, clear job description, job security, incentives and rewards could positively lead to higher work engagement and employee well-being (Teo et al , 2020; Murphy et al , 2018). Similarly, the implementation of HCWS was found to relate to work engagement and job satisfaction and high commitment (Sharma, 2021; Teo et al , 2020). A more recent study (Chen et al , 2021; Karatepe et al , 2018) also found high-involvement human resource (HR) practices, a construct related to HCWS, to have significant positive effects on work engagement and job satisfaction.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations